Photochemical Behavior and Photolysis of Protonated Forms of Levofloxacin. (14th September 2013) - Polishchuk, Anna; Emelina, Tatyna; Karaseva, Emilya; Cramariuc, Oana; Chukharev, Vladimir; Karasev, Vladimir
Abstract The effect of intermolecular proton transfer on the spectral properties of levofloxacin in the ground and excited electronic states was studied. The preferred direction of possible protolytic reactions induced by UV irradiation in this compound was studied. It was found that the proton transfer processes have a considerable effect on the capability of the compound to emit light and occur on the nanosecond timescale. The photochemical reactions of the tree forms of levofloxacin (pH: 4.0, 7.0, 10.0) were studied by laser flash photolysis and product studies. Irradiation at pH 4 yielded a pulse and transient (λmax = 395, 515, 575 nm) assigned to the protonated triplet. Irradiation at pH 7 yielded a transient species (λmax = 525, 610 nm) assigned to the neutral form. Protonation of the anionic singlet excited state was also observed (λmax = 440, 570, 680 nm).